Knockdown of SEMA7A alleviates MPP+‐induced apoptosis and inflammation in BV2 microglia via PPAR‐γ activation and MAPK inactivation - Weinan Qi; Dan Zeng; Xiaoshuan Xiong; Qun Hu (Immunity, Inflammation and Disease)
Abstract Introduction The inflammation mediated by microglial cells plays an important role in the process of neurodegenerative diseases. Recent evidence indicates that semaphorin 7A (SEMA7A) is implicated in various neurodegenerative diseases, but whether it plays a role in Parkinson's disease (PD) remains unclear. Methods In this study, 1.0 mmol/L 1‐methyl‐4‐phenylpyridinium (MPP+)‐stimulated mouse microglia (BV2) cells were used as an in vitro model of PD. The expression of SEMA7A was detected by quantitative polymerase chain reaction. Cell Counting Kit‐8 and apoptosis kits were used to analyze the viability and apoptosis of BV‐2 cells. The content of IL‐6, IL‐β, and tumor necrosis factor‐α was determined by ELISA (enzyme‐linked immunosorbent assay) kit. Western blot was used to detect the protein expression level of the inducible NO synthase and cyclooxygenase‐2. Results Our findings indicated that SEMA7A expression in BV2 cells was upregulated after MPP+ stimulation. Knockdown of SEMA7A promoted cell viability while it inhibited apoptosis and the expression of proinflammatory enzymes and proinflammatory cytokines. Silencing SEMA7A‐induced peroxisome proliferator‐activated receptor‐gamma (PPAR‐γ) activation and mitogen‐activated protein kinase (MAPK) signaling pathway inactivation. Furthermore, a PPAR‐γ inhibitor and an MAPK activator promoted the effect of MPP+ on cell viability, apoptosis, and inflammation of BV2 cells; what is more, the PPAR‐γ inhibitor and MAPK activator blocked the inhibitory effect of SEMA7A downregulation on MPP+‐induced injury. Conclusion In general, knockdown of SEMA7A inhibits MPP+‐induced BV2 cell apoptosis and inflammation via PPAR‐γ activation and MAPK inactivation, which may provide a new therapy target for PD.